2007
DOI: 10.1007/s10875-007-9131-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Homozygous DC-SIGNR 5/5 Tandem Repeat Polymorphism in HIV-1 Exposed Seronegative North Indian Individuals

Abstract: Despite multiple sexual exposures to HIV-1 virus, some individuals remain HIV-1 seronegative. Although several genetic factors have been related to HIV-1 resistance, the homozygosity for a mutation in CCR5 gene (the 32-bp deletion, i.e., CCR5-Delta32 allele) is presently considered the most relevant one. The C-type lectins, DC-SIGN (present on dendritic cells and macrophages) and DC-SIGNR (present on endothelial cells in liver and lymph nodes) efficiently bind and transmit HIV-1 to susceptible cell in trans, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…No differences in genotype distribution were found when comparing HIV + and HIV À children, however we observed that the 5/5, 6/6 and homozygous genotypes were significantly more frequent in HIV + children than healthy controls. Even if our findings evidenced a lack of association between L-SIGN gene polymorphisms and HIV vertical transmission, the different distribution of L-SIGN exon 4 alleles in HIV + and unexposed uninfected children may however suggest a possible involvement of L-SIGN in HIV infection, as reported in other studies [12,19,31] In Table 5 we summarize the main association reported up to now for DC-SIGN and HIV-1 infections in different populations. The different findings obtained in distinct populations indicate that ethnicity can play a role in the genetic susceptibility to HIV vertical transmission, a complex and multifactorial trait, so replica studies are needed.…”
Section: L-signmentioning
confidence: 45%
See 3 more Smart Citations
“…No differences in genotype distribution were found when comparing HIV + and HIV À children, however we observed that the 5/5, 6/6 and homozygous genotypes were significantly more frequent in HIV + children than healthy controls. Even if our findings evidenced a lack of association between L-SIGN gene polymorphisms and HIV vertical transmission, the different distribution of L-SIGN exon 4 alleles in HIV + and unexposed uninfected children may however suggest a possible involvement of L-SIGN in HIV infection, as reported in other studies [12,19,31] In Table 5 we summarize the main association reported up to now for DC-SIGN and HIV-1 infections in different populations. The different findings obtained in distinct populations indicate that ethnicity can play a role in the genetic susceptibility to HIV vertical transmission, a complex and multifactorial trait, so replica studies are needed.…”
Section: L-signmentioning
confidence: 45%
“…Different studies have shown that polymorphisms in DC-SIGN and L-SIGN genes can influence susceptibility and/or resistance to HIV-1 [11][12][13]18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV-1 infected individuals have widely different rates of disease progression and several SNPs are reported to be effective in different clinical stages of HIV/AIDS patients. Among North Indians, we recently reported that homozygous DC-SIGNR 5/5 showed significant reduced risk of HIV-1 infection [Rathore et al, 2008a] while repeat region polymorphism in the DC-SIGN neck domain does not effect risk of HIV-1 transmission [Rathore et al, 2008b]. Till date, only single study was conducted in which effect of RANTES genetic variants was assessed for HIV/AIDS transmission among North Indians [Suresh et al, 2006].…”
Section: Introductionmentioning
confidence: 99%